Pengaruh Beban Kerja Dan Stres Kerja Terhadap Turnover Intention Pada PT. Global Cool - Salsabila Taqwaning Afifi; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri; Dewi Puspaningtyas Faeni; Indah Rizki Maulia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine the effect of workload and work stress on turnover intention at PT Global Cool. The research method used is quantitative research. The sampling technique used is saturated sampling technique, while the total population in this study is 65 respondents. Data analysis using Smart PLS 3.0 software and testing is carried out, namely data analysis methods (descriptive and verification), measurement model evaluation (outer model), namely validity and reliability tests, structural model evaluation (inner model) and hypothesis testing. The results show that 1) workload has a significant effect on turnover intention 2) work stress has a significant effect on turnover intention 3) workload and work stress have a significant effect simultaneously on turnover intention.